PENGEMBANGAN TEKNOLOGI OPTICAL CHARACTER RECOGNITION DI FLUTTER BERUPA DETEKSI TEKS PADA GAMBAR - Shierly Mayco Angela; Ade Eviyanti; Metatia Intan Mauliana (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This research aims to develop Optical Character Recognition (OCR) technology integrated with the Flutter platform to detect text in images in mobile applications. OCR technology allows extracting text from images automatically, eliminating the need for manual intervention, and is implemented using the Tesseract OCR library which is known to have a high level of accuracy. By combining Flutter, a multi-platform application development framework developed by Google, this research produces an application that is able to detect text from images taken via the kamera or cell phone gallery with fast response and high accuracy. The Rapid Application Development (RAD) approach was used in developing this system. Research stages include requirements planning, system design, system development, and implementation. System testing is carried out using the Black box testing method to ensure all features work according to specifications, as well as User Acceptance Testing (UAT) to assess user satisfaction. The test results show that the application runs well and is accepted by users with a strongly agree level of approval (88%). This research contributes to creating an efficient and intelligent mobile application for detecting text in images, which can be used for various purposes, such as searching for digital comic references, detecting text on food menus, and identifying vehicle number plates.